2023
DOI: 10.1186/s12903-023-03294-3
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy (PDT) for oral leukoplakia: a systematic review and meta-analysis of single-arm studies examining efficacy and subgroup analyses

Abstract: Objective This study aims to evaluate the efficacy of photodynamic therapy (PDT) in the treatment of oral leukoplakia and explore the subgroup factors that may influence its effectiveness. Methods A systematic search was conducted in PubMed, Embase, the Cochrane Library, and Web of Science databases to identify relevant studies. Meta-analysis was performed using Stata15.0 software. Cochran’s Q test and I2 statistics were used to evaluate heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Of 354 patients with complete response (CR) after treatment with PDT, recurrence was observed in 71 patients, and then the pooled recurrence rate (95% confidence interval [CI]) was 20.1% (16.2–24.6%). In the recent systematic review and meta-analysis, the pooled recurrence rate (95%CI) of oral leukoplakia patients received PDT was reported to be 13% (8–18%); 3 the pooled recurrence rate (95%CI) of oral leukoplakia and erythroplakia received PDT was reported to be 22.3% (16.1–29.9%). 4 Besides, we recently reported the pooled recurrence rate (95%CI) of OPL patients received scalpel surgery and laser therapy was 29.5% (26.3–33.0%) and 32.2% (26.1–38.9%), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 354 patients with complete response (CR) after treatment with PDT, recurrence was observed in 71 patients, and then the pooled recurrence rate (95% confidence interval [CI]) was 20.1% (16.2–24.6%). In the recent systematic review and meta-analysis, the pooled recurrence rate (95%CI) of oral leukoplakia patients received PDT was reported to be 13% (8–18%); 3 the pooled recurrence rate (95%CI) of oral leukoplakia and erythroplakia received PDT was reported to be 22.3% (16.1–29.9%). 4 Besides, we recently reported the pooled recurrence rate (95%CI) of OPL patients received scalpel surgery and laser therapy was 29.5% (26.3–33.0%) and 32.2% (26.1–38.9%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Photodynamic therapy (PDT) is a minimally invasive treatment that uses exogenous light with a specific wavelength and photosensitizers to create molecular oxygen, which causes the death of tissue cells by necrosis, apoptosis, or autophagia. 3 In the recent updated systematic review and meta-analysis, the efficacies of PDT in the treatment of both oral leukoplakia and all oral potentially malignant disorders (including oral leukoplakia, erythroplakia, lichen planus, verrucous hyperplasia, actinic cheilitis) patients were systematically assessed. 3 , 4 Notably, clinical response (complete-, partial-, or no response) was the main outcome measure assessed in all the studies, recurrence was the secondary outcome measure assessed in a portion of the previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, PDT alone exhibits lower efficacy in managing OLK. Previous meta-analyses have indicated that PDT alone is effective in OLK management but has no clear advantage over surgery [ 56 , 57 ]. The diminished efficacy of PDT alone can be attributed to the poor penetration of the photosensitizer and the low absorption efficiency of the tissue.…”
Section: Discussionmentioning
confidence: 99%